Meningkatkan Komitmen Afektif melalui Cerita Sukses Organisasi - Yayik Novitriami; Thomas Dicky Hastjarjo (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2015)
The aim of this study was to determine the extent to which affective commit¬ment could be increased through the storytelling method about organization success stories. Pretest-postest contrl group design was used i this study. Analysis of covariance and mixed analysis of variance were statistical tehniques to analyze data. The subjects were 56 employees with a minimum tenure of three years and were assigned into experimental and control groups. The experimental group was received storytelling about organization success story where as the control group did not receive any treatment. The level of affective commitment was measured by affective commitment scale. The measurement was conducted before and after the storytelling. Results of this research shows that there was a difference on affective commitment scores between experiment and control group as a result of the storytelling (F=12,995; p<.05). However, tenure does not affect the treatment of storytelling method about organization success story in order to increase the employee’s affective commitment (F=14.79; p<.01).